China‘s Climate Change Policy Strengthening Its Diplomacy - Wulansari, Ica (Universitas Muhammadiyah Yogyakarta, 2016)
This research attempts to examine China‘s climate change diplomacy. This paper also observes how China strengthens its interest in line with the speed of climate change impact. China should consider climate change as the threat for its national interest since it impacted to its rapid economic growth. Currently, China’s use of fossil fuel has produced the significant amount of carbon dioxide emissions. In response to this, China considered to strengthen its energy policy as a way to reduce emission through The National Development and Reform Commission (NDRC) whose job is to confirm that mitigation and adoption of climate change are standardized. Furthermore, China has issued the principle of equity in 2009 by strengthening the responsibility for historical emissions of the developed countries and the future emissions rights of the developing countries. At the international level, China played a strategic and significant role in Conference of Parties in UNFCC (United Nations Framework Convention on Climate Change). In addition, deepening a climate change cooperation with the United States was also at China’s lists.